THE EFFECT OF GOOD CORPORATE GOVERNANCE IMPLEMENTATION ON FINANCIAL PERFORMANCE - Tasya Tia Tamara; Haninun Haninun; Aminah Aminah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This research is based on the drive to understand the impact of good corporate governance (GCG) on earnings outcomes, providing a key foundation for further exploration in the context of financial organizations. The main focus of this research is on corporate governance principles, the role of audit committees, board autonomy, as well as aspects of financial performance such as capitalization and financial ratios. With a research timeframe involving data from 2017 to 2021, this study details an in-depth analysis of 39 banks and other financial organizations that have shares in the Indonesian market. The main findings of the study show a favorable and statistically significant correlation between the percentage of ownership held by institutional investors and the financial performance of the company. Involving aspects such as capitalization and financial ratios, the study reveals a meaningful link between solid corporate governance and positive earnings results. However, there were interesting findings regarding return on equity (ROE), a key indicator of financial success. The research showed that ROE was not affected by the independent committee variable, highlighting the complexity of the relationship between GCG elements and certain financial indicators. In contrast, the audit committee variable was shown to have a positive and statistically significant impact on financial performance, suggesting a strong role in mitigating risk and increasing transparency in corporate management.